2021
DOI: 10.1111/1756-185x.14051
|View full text |Cite
|
Sign up to set email alerts
|

A patient‐centered knowledge translation tool for treat‐to‐target strategy in rheumatoid arthritis: Patient and rheumatologist perspectives

Abstract: Aim Implementation of treat‐to‐target (T2T) for rheumatoid arthritis (RA) presents many challenges and an evidence‐practice gap has emerged. This study assessed clinician and patient barriers to the implementation of an RA‐T2T strategy and developed a knowledge translation (KT) tool for use in “real‐life” clinical settings. Methods Surveys of patients and rheumatologists measured agreement with RA‐T2T recommendations and use in daily practice. Patient knowledge and perceptions were assessed as was clinician wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…One year in review 2021: novelties in the treatment of rheumatoid arthritis E. Silvagni 1 , G. Sakellariou 2 , A. Bortoluzzi 1 , A. Giollo 3,4 , N. Ughi 5 , L. Vultaggio 1 , C.A. Scirè 1,6 Treatment novelties in RA / E. Silvagni et al…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…One year in review 2021: novelties in the treatment of rheumatoid arthritis E. Silvagni 1 , G. Sakellariou 2 , A. Bortoluzzi 1 , A. Giollo 3,4 , N. Ughi 5 , L. Vultaggio 1 , C.A. Scirè 1,6 Treatment novelties in RA / E. Silvagni et al…”
Section: Reviewmentioning
confidence: 99%
“…An Australian initiative has developed and tested a patient-centred knowledge translation tool for T2T in RA, providing usable information to engage patients in the process of care (6). A Maximum Difference Scaling exercise including patients with inflammatory arthritis from the Netherlands showed that the main factors associated with adherence to treatment were related to reducing symptoms, maintaining independency and shared decision making, while practical issues were least important for RA patients to adhere to medications (7).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of biologic treatment for severe CSU has gathered momentum in the UK NHS in recent years and is based on National Institute of Health and Clinical Excellence (NICE) guidelines. Recent UK experience suggests a requirement for multiple treatment courses in a majority of patients with severe CSU 8 and use of treat‐to‐target concept 9 may be better applied in biologic‐resistant cases. The BRIT registry provides an opportunity to generate such datasets prospectively to enable strategic planning of resource allocation for specialist allergy centres.…”
Section: Advantages Of Britmentioning
confidence: 99%